Pelatihan Pemasaran Digital dan Pengembangan Web untuk Mendukung Penjualan Komoditas Porang pada Kelompok Tani Yin Porang di Wonogiri - Almuntaha, Eska; Mawadati, Argaditia; Lestari, Nidia; Purwanto, Yuli; Raharjo, Suwanto; Setyaningsih, Emy; Rahayu, Suparni Setyowati; Purnawan; Dzakiya, Nurul (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
If appropriately processed, Amorphophallus muelleri Bl. or porang can produce many benefits. Economically, porang commodity is very promising because it has economic value, especially for industry and health. Porang is a raw material for the cosmetic industry and a favorite low-calorie food ingredient, especially in Japan and South Korea. Yin Porrang Farmer Group is one of the porang farmer groups in Padarangin Village, Slogohimo District, Wonogiri Regency, Central Java. In addition to the final product problem, conventional marketing is a significant problem for the business development of this farmer group. IST AKPRIND, through the Matching Fund program in 2021, offers solutions for product development to increase the selling value of porang. Digital marketing training and web development as a digital marketing tool also carried out to reach a broader target market at a lower cost and in a more scalable way.